The Aberration of the Third Quest of Historical Jesus - Nathanael Xuesheng WANG , (Journal of Research for Christianity in China (JRCC), 2024)
The past two hundred years have witnessed five distinct scholarly phases in the quest for the historical Jesus, with the “Third Quest” emerging as the preeminent approach within contemporary New Testament Studies. Proponents of the Third Quest commendably situate Jesus within his Jewish milieu, recognizing him as a Jewish eschatological apocalyptic prophet. Nonetheless, there is a tendency among these scholars to accentuate the “Jewishness” of Jesus excessively, at times bordering on the realm of “political correctness”. Such an overemphasis risks introducing bias and undermining the objectivity essential to historical inquiry. This paper offers a critical examination of the Third Quest’s undue stress on the “Jewishness” of Jesus, positing that Jesus and his followers manifested distinctive characteristics that set them apart from contemporary groups such as the Pharisees and the Essenes. It is posited that a balanced appreciation of Jesus’ Jewish identity, in harmony with his uniqueness, provides a more coherent explanation for the distinctive narratives found in the New Testament, the genesis of Christianity, and its eventual divergence from Judaism.